Providing Services to Women in Situations of Prostitution and Human Trafficking during the COVID-19 Pandemic in Spain, Italy, and Portugal - García-Vázquez, Olaya; Meneses-Falcón, Carmen (Anti-Trafficking Review, 2023)
This short article discusses the challenges faced by women engaging in prostitution/sex work or in situations of trafficking for sexual exploitation during the COVID-19 pandemic. These included housing and food insecurity, violence, failure by the police to identify them as trafficked persons, lack of social assistance, and the inability to renew residence and work permits. The article also presents the support provided to women by the NGO Hermanas Oblatas in Spain, Portugal, and Italy.